Basal myokine levels are associated with quality of life and depressed mood in older adults. (2nd March 2021) - Mucher, Patrick; Batmyagmar, Delgerdalai; Perkmann, Thomas; Repl, Manuela; Radakovics, Astrid; Ponocny‐Seliger, Elisabeth; Lukas, Ina; Fritzer‐Szekeres, Monika; Lehrner, Johann; Knogler, Thomas; Tscholakoff, Dimiter; Fondi, Martina; et al.
Abstract: In an aging society, late‐life depression has become an increasing problem. There is evidence that physical activity ameliorates depressive symptoms and increases the quality of life (QoL). However, the underlying mechanisms are still poorly understood. Myokines are molecules secreted in response to muscle contraction. Some of them can cross the blood‐brain barrier, making them promising candidates for mediating the beneficial effects of physical activity on mood. The present study aims to compare circulating myokine levels to depression/QoL in older athletes and controls. 55 athletes, 57 controls >59 years were enrolled. The assessment included ergometry, magnetic resonance imaging, blood withdrawal, and neuropsychological testing. Serum interleukin‐6 (IL‐6), irisin, brain‐derived neurotrophic factor (BDNF), kynurenine, and cathepsin B were analyzed and compared to surrogates of depression and quality of life. Athletes presented with higher levels of Cathepsin B. Among controls, all myokines but irisin were associated with age. Also, among controls, kynurenine and IL‐6 correlated inversely with specific dimensions of quality of life questionnaires, and IL‐6 further with depressive symptoms and decreased physical performance. No such associations could be found among athletes. Irisin levels were inversely associated with mild depression and low‐grade white matter‐lesions in the brain and predicted impaired QoL. The circulating levels of several myokines/muscle activity‐related factors appear to be associated with depressive symptoms and impaired QoL among older adults. However, in athletes, some of these connections seem ameliorated, suggesting additional stressors (as f.e. age) or a different pathomechanism among athletes. Impact Statement: Physical exercise positively affects mood and quality of life, however, the underlying mechanisms are not yet fully understood. Myokines are released in response to muscle contraction. They might be promising candidates for mediating muscle‐brain‐crosstalk. Our results suggest that basal kynurenine and interleukin‐6 levels are correlated with poor quality of life and/or depressive symptoms. In contrast, low irisin levels were associated with mild depression and low‐grade white matter‐hyperintensities in brain MRIs and they predicted impaired quality of life.